INFLUENCE OF SELEGILIN - SELECTIV INHIBITOR OF MONOAMINOXYDASE-B ON CIRCADIAN RHYTM KIDNEY FUNCTION AFTER BLOCKIND CENTRAL PACEMAKER - Dotsyuk, L.G.; Kushnir, I.G. (World of Medicine and Biology, 2012)
In experiments on rats was established that after blocade of central pacemaker kidney preserve elements of circadian rhytm and adequate response to dopamine. Was conclused about important role of glomerulo-tubular and tubulo-tubular balance in this process.
Keywords: circadian rhytm; dopamin; glomerulo-tubular balance